MINIMIZING OXIDATION AND MICROBIAL CONTENT IN BEEF SAUSAGES THROUGH THE INCLUSION OF SENDUDUK (Melastoma malabathricum L) LEAF POWDER - Suharyanto, Suharyanto; Warnoto, Warnoto; Prabowo, Primananda; Hadis, Aris Akhludin; Hajrawati, Hajrawati (BPFP Faperta UNIB, 2025)
Sausages are a popular food item in Indonesia, often sold by vendors along the roadside or in wheelbarrows. However, this selling method carries a risk of contamination, which can lead to spoilage. While synthetic preservatives can help, they may also pose health risks to consumers. The addition of natural ingredients, such as senduduk (Melastoma malabathricum L.) leaf powder (SLP), into sausage production, can be an alternative solution. This study aimed to evaluate the effects of SLP on the oxidation, microbial content, and physical properties of beef sausages. This study used a Completely Randomized Design with varying concentrations of SLP (0%, 0.5%, 1%, and 1.5% w/w) across four replications. The Thiobarbituric Acid (TBA) number, Total Plate Count (TPC), pH, cooking yield, water holding capacity (WHC), tenderness, and folding test were determined. The results demonstrated that adding SLP effectively reduced both the TBA number and the total plate count in the sausages at all tested concentrations. It also lowered the pH on the first day of storage and decreased the water holding capacity (WHC) when added at a concentration of 1.5%. Additionally, it influenced the results of the folding test. However, no significant differences were observed in the cooking yield and tenderness of the sausages. In conclusion, the addition of SLP into sausage production can effectively reduce oxidation and microbial content in beef sausages.